2023
DOI: 10.1001/jamanetworkopen.2023.0090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Concomitant Systemic Treatment in Older Adults With Head and Neck Squamous Cell Carcinoma Undergoing Definitive Radiotherapy

Abstract: ImportanceThe number of older adults with head and neck squamous cell carcinoma (HNSCC) is increasing, and these patients are underrepresented in clinical trials. It is unclear whether the addition of chemotherapy or cetuximab to radiotherapy is associated with improved survival in older adults with HNSCC.ObjectiveTo examine whether the addition of chemotherapy or cetuximab to definitive radiotherapy is associated with improved survival in patients with locoregionally advanced (LA) HNSCC.Design, Setting, and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…On univariate analysis, both ECOG 0‐1 and CCI < 6 was associated with improved OS, and on multivariate analysis only the CCI < 6 was associated with improved OS. In a large multi‐institutional study of head and neck cancer patients ≥65 years, the patients who most benefited from CRT were those who had a better ECOG PS 16 . In an older study of the Surveillance, Epidemiology, and End Results database, CCI was shown to be associated with survival and inferior OS with higher scores 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On univariate analysis, both ECOG 0‐1 and CCI < 6 was associated with improved OS, and on multivariate analysis only the CCI < 6 was associated with improved OS. In a large multi‐institutional study of head and neck cancer patients ≥65 years, the patients who most benefited from CRT were those who had a better ECOG PS 16 . In an older study of the Surveillance, Epidemiology, and End Results database, CCI was shown to be associated with survival and inferior OS with higher scores 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In a large multi-institutional study of head and neck cancer patients ≥65 years, the patients who most benefited from CRT were those who had a better ECOG PS. 16 In an older study of the Surveillance, Epidemiology, and End Results database, CCI was shown to be associated with survival and inferior OS with higher scores. 17 Given the importance of identifying elderly head and neck cancer patients at risk for adverse outcomes, there has been increasing interest in incorporating geriatric assessments to stratify patients who may be suitable for aggressive treatment.…”
Section: Late Toxicity (>90 Days)mentioning
confidence: 99%
“…[ 4,5 ] Radiation therapy offers hope for lesions that are challenging to remove surgically, while it often introduces additional issues, such as skin inflammation and fibrosis. [ 6 ] Moreover, the limited success and severe adverse effects associated with chemotherapy further underscore the need to develop a safer and more effective treatment strategy for CSCC. [ 7,8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Our team has been part of a larger multinational effort to define the optimal chemotherapy regimens in elderly patients with locoregionally advanced HNSCC. 3,4 These efforts to leverage large datasets in a multicenter patient cohort will provide the power to determine important prognostic factors in HNSCC. Finally, outcomes after progression and the use of salvage therapies would be interesting but were beyond the scope of the current study.…”
mentioning
confidence: 99%